Behavior of Reinforced Concrete Frames In-Filled with Lightweight Materials Under Seismic Loads - Iswandi Imran; Aris Aryanto (Institute of Research and Community Outreach - Petra Christian University, 2009)
This paper presents an experimental and analytical research conducted to study the in-plane behavior of reinforced concrete (R/C) frames in-filled with lightweight materials. The tests were performed on two single bay, single story in-filled frame specimens with ½ scale models. One of the test specimens was in-filled with lightweight materials, i.e. autoclaved aerated concrete (AAC) blocks, and the other, used as the comparison, was in-filled with clay brick materials. The loading used in the tests was in the form of cyclic in-plane lateral loads, simulating earthquake forces. Behavior of the frame structures was evaluated through the observed strength and deformation characteristics, the measured hysteretic energy dissipation capacity and the measured ductility. The experimental results show that the R/C frame in-filled with AAC blocks exhibited better performance under in-plane lateral loads than that in-filled with conventional clay bricks. In the analytical work, the performance of some analytical models available in the literature was evaluated in simulating the experimental results